Genome assembly of Klebsiella michiganensis based on metagenomic next-generation sequencing reveals its genomic characteristics in population genetics and molecular epidemiology - Sun, Yong; Cai, Qingqing; Li, Tianyu; Chen, Jingbo; Fang, Yuan (Frontiers in Microbiology, 2025)
IntroductionKlebsiella michiganensis, a significant member of the Klebsiella oxytoca complex, has emerged as a potential pathogen in clinical settings. Despite extensive research on the Klebsiella pneumoniae complex, the pathogenicity and drug resistance of the K. oxytoca complex remain understudied, particularly regarding the reconstruction of whole genomes from metagenomic next-generation sequencing (mNGS) data.MethodsIn this study, bronchoalveolar lavage fluid (BALF) from a 55-year-old woman with a suspected right lung infection in Anhui Province, China, was analyzed using mNGS.ResultsThree distinct assembly strategies were employed to reconstruct the genome of K. michiganensis, leading to the identification of a novel ST452 strain, KMLRT2206. Comprehensive genomic analysis of this strain and 206 clinical isolates (genomes downloaded from public databases) revealed the population structure, distribution of drug resistance genes, and virulence factors of K. michiganensis. The results demonstrated significant genetic diversity, with the species divided into three major clades, each exhibiting distinct patterns of drug resistance and virulence genes. Notably, 38.6% of the strains harbored the blaOXY–1–1 gene, highlighting a potential threat of drug resistance. While virulence gene distribution was not correlated with sequence type (ST), significant differences were observed among clades.ConclusionThis study underscores the value of mNGS combined with optimized assembly strategies for accurate species identification within the K. oxytoca complex, providing critical insights for clinical pathogen detection and epidemiological surveillance.